Pemanfaatan Limbah Kotoran Domba Dan Kambing Untuk Produksi Pupuk Organik Pada Kelompok Ternak Sidomulyo Desa Suci Kecamatan Panti Kabupaten Jember - Hudori, Huda Ahmad; Wiyono, Luluk Cahyo; Dhandy, Rahmat; Sholihah, Elis Rahmawati Mar’atus; Wati, Cicik Retno (Politeknik Negeri Jember, 2025)
Sheep and goat farming has enormous economic potential if managed properly. Livestock waste can be processed into organic fertilizer, biogas, or raw materials for other innovative products with high economic value. This community service program will be carried out in the Sidomulya livestock group in Suci Village, Panti District, with a total of 25 sheep and goat farmers, as an effort to increase the empowerment of the role of mothers in maintaining environmental sustainability. The purpose of this community service activity is to utilize livestock waste to reduce the negative impact of livestock waste on environmental pollution through waste management activities including good livestock management, especially in handling waste, the process of recycling livestock waste (recycling) on a home and group scale to improve starting from sheep waste, through empowering livestock group members. The method of implementing the community service activity is carried out through several stages, namely lectures, discussions, demonstrations, direct practice, and observation. The results of this activity are expected to change community behavior from waste disposal to productive processing, which contributes to the broader goals of community service, namely village economic empowerment and environmental preservation in rural Jember.